2017
DOI: 10.1111/jar.12424
|View full text |Cite
|
Sign up to set email alerts
|

The role of shame in the development and maintenance of psychological distress in adults with intellectual disabilities: A narrative review and synthesis

Abstract: Shame may be a contributory factor in the development and maintenance of psychological distress and subsequent mental health issues in some adults with mild-to-moderate intellectual disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 100 publications
(257 reference statements)
0
32
0
1
Order By: Relevance
“…In addition, psychological distress being instrumental between shame and well-being may be explained by the fact that shamed individuals are passive against distress. In addition, it can be deduced that shame for mediation may make individuals vulnerable to psychological distresses, such as depression, anxiety, etc., and, hence, their well-being can be adversely affected (Clapton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, psychological distress being instrumental between shame and well-being may be explained by the fact that shamed individuals are passive against distress. In addition, it can be deduced that shame for mediation may make individuals vulnerable to psychological distresses, such as depression, anxiety, etc., and, hence, their well-being can be adversely affected (Clapton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies indicated that external shame may increase psychological distress (e.g., Castilho et al, 2017;Kim et al, 2011), and also may reduce well-being (Cibich et al, 2016;Varghese, 2015). Moreover, relevant literature showed that shame may reduce wellbeing via psychological distress (e.g., Clapton et al, 2018). Therefore, we tested the meditational model with external shame as an independent variable, depression, anxiety, and stress as mediator variables and subjective well-being as a dependent variable.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to women in particular, Araújo, Meira and Almeida [28, p. 419] conclude from their research across many countries that "Some appearance stereotypes… in the physical world follow [women] in the online world". Negative experiences, such as continually being passed over in favour of others, is known to be damaging to a person's sexual self-esteem, especially if they are already vulnerable [29] and can cause people to experience shame [30].…”
Section: Mainstream Dating Agencies and Online Datingmentioning
confidence: 99%